Doctoral Student Research Alliance: Unexpected Challenges in Group Formation - Tara Chavez; John Wade; Scott W. Greenberger (Journal of Scholarly Engagement, 2020)
The purpose of this reflective practice is to explore the unexpected difficulty experienced by two student members, Tara and John, and their faculty mentor of the fledgling Doctoral Student Research Alliance (DSRA) at a university in the Southwestern United States. The identified problem is the unexpected difficulty in forming the DSRA group. The following are the proposed reasons for the problem: (a) program format, (b) family and professional obligations, (c) group dynamics, and (d) identifying a mentor. In evaluating the reasons, the issue of scheduling conflicts is identified as central to all of the reasons. The identification of imposter syndrome is one surprising insight from the reflective practice. Future research is recommended to explore the effect of imposter syndrome on doctoral student participation, specifically in participation on research teams; to examine more thoroughly the role of faculty mentors in doctoral student development, specifically as it relates to small group dynamics; and to investigate the effect of scheduling conflicts and other challenges on the longevity of mentor driven doctoral research groups. Keywords: imposter syndrome, group dynamics, mentorship, scheduling conflicts